Production, Optimization, and Partial Purification of Cellulases by Penicillium expansum Fermented with Industrial Sugar Cane Bagasse - Sial, Muhammad Uris; Noomrio, Muhammad Hanif (Indus Journal of Bioscience Research, 2025)
There is an extensive use of biological substances such as enzymes in a variety of industrial and medicinal fields. Cellulase, has gained much interest worldwide as it’s a biocatalyst for converting cellulose into simple sugars. The present was designed to explore and develop the renewable energy resources. The bagasse as agro-waste offers as an economical and sustainable substrate for cellulase synthesis. Acidic conditions (pH 6.0) hydrolyzed the bagasse, which was evident from the fungal growth and the considerable enzyme activity. Cellulase yields of up to 3782.5, 3798.5, and 3491.5 units/mL were recorded during a 240-hour incubation period, at a 28°C optimal temperature. To improve the celluloses produced by P. expansum, 0.02% maltose and 0.001% thiamine were added to sugar cane bagasse that had been pretreated with 0.6N NaOH in the mineral media. Sephadex G-100 chromatography was used to isolate five fractions and separated through SDS polyacrylamide gel electrophoresis. This study shows that CM-cellulases, β-glucosidase, and salicinase are among the cellulolytic enzymes produced by P. expansum. These cellulases have an acidic, neutral, and alkaline pH, according to experimental research. While some cellulases are heat stable and preserve more than 20–25% of their activities at 100°C, others are heat labile and lose about 60% of their activities at that temperature. Cellulase possesses the property of being metalloenzymes, meaning that their active center has both a thio and a sulfhydral group. Herein, we are reporting the use of bagasse as carbon source for microbes. Ultimately, highlighting the use of microbes in stable and effective production of cellulases or other important biomolecules of biomedical importance.